Impact of Ocean Acidification on Energy Metabolism of Oyster, Crassostrea gigas—Changes in Metabolic Pathways and Thermal Response - Christian Bock; Inna M. Sokolova; Silke Eilers; Hans O. Pörtner; Gisela Lannig (Marine Drugs, 2010)
Climate change with increasing temperature and ocean acidification (OA) poses risks for marine ecosystems. According to Pörtner and Farrell [1], synergistic effects of elevated temperature and CO2-induced OA on energy metabolism will narrow the thermal tolerance window of marine ectothermal animals. To test this hypothesis, we investigated the effect of an acute temperature rise on energy metabolism of the oyster, Crassostrea gigas chronically exposed to elevated CO2 levels (partial pressure of CO2 in the seawater ~0.15 kPa, seawater pH ~ 7.7). Within one month of incubation at elevated PCO2 and 15 °C hemolymph pH fell (pHe = 7.1 ± 0.2 (CO2-group) vs. 7.6 ± 0.1 (control)) and PeCO2 values in hemolymph increased (0.5 ± 0.2 kPa (CO2-group) vs. 0.2 ± 0.04 kPa (control)). Slightly but significantly elevated bicarbonate concentrations in the hemolymph of CO2-incubated oysters ([HCO-3]e = 1.8 ± 0.3 mM (CO2-group) vs. 1.3 ± 0.1 mM (control)) indicate only minimal regulation of extracellular acid-base status. At the acclimation temperature of 15 °C the OA-induced decrease in pHe did not lead to metabolic depression in oysters as standard metabolism rates (SMR) of CO2-exposed oysters were similar to controls. Upon acute warming SMR rose in both groups, but displayed a stronger increase in the CO2-incubated group. Investigation in isolated gill cells revealed a similar temperature-dependence of respiration between groups. Furthermore, the fraction of cellular energy demand for ion regulation via Na+/K+-ATPase was not affected by chronic hypercapnia or temperature. Metabolic profiling using 1H-NMR spectroscopy revealed substantial changes in some tissues following OA exposure at 15 °C. In mantle tissue alanine and ATP levels decreased significantly whereas an increase in succinate levels was observed in gill tissue. These findings suggest shifts in metabolic pathways following OA-exposure. Our study confirms that OA affects energy metabolism in oysters and suggests that climate change may affect populations of sessile coastal invertebrates such as mollusks.